KEMAMPUAN MENULIS KARANGAN BERBAHASA BUGIS SISWA KELAS XI SMAN 1 PANGKAJENE - Zulkifli; Amir, Johar; Yunus, Andi Fatimah (Journal Studies in Indonesian Language and Literature, 2024)
The purpose of this study was to describe the ability to write narrative essay in Bugis language of students of class XI of SMAN 1 Pangkajene. This type of research is quantitative research in the form of descriptive quantitative. The population in this study were all students of class XI SMAN 1 Pangkajene which amounted to 344 people with 10 classes. The sample set is class XI. Good as many as 36 students using simple random sampling technique. The data collection technique used is the test technique, namely the test. The data collected will be analyzed using descriptive statistical techniques. The results showed that the ability to write narrative essays in Bugis language of students of class XI of SMAN 1 Pangkajene was declared incapable. It can be seen from the percentage of students who scored ≥ 75 in the able category did not reach the set criteria of 75%. Instead, it only amounted to 36%.